2018
DOI: 10.5853/jos.2017.01802
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Statin Use and the Risk of Stroke or Transient Ischemic Attack after Radiotherapy for Head and Neck Cancer

Abstract: Background and Purpose Interventions to reduce the risk for cerebrovascular events (CVE; stroke and transient ischemic attack [TIA]) after radiotherapy (RT) for head and neck cancer (HNCA) are needed. Among broad populations, statins reduce CVEs; however, whether statins reduce CVEs after RT for HNCA is unclear. Therefore, we aimed to test whether incidental statin use at the time of RT is associated with a lower rate of CVEs after RT for HNCA.Methods From an institutional database we identified all consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
1
33
1
Order By: Relevance
“…The preliminary findings from this study showed that the legacy effect of statin during radiotherapy does not lower the subsequent risk of TIA and ischemic stroke in patient with HNC, which is contradictory to the report by Addison et al [ 1 ] Our study population, which comprised mostly of Asians, was different from that of Addison’s, and the different ethnic background may contribute to divergent statin resistance. Moreover, nasopharyngeal carcinoma consisted of a significant proportion of HNC in Taiwan [ 2 ].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The preliminary findings from this study showed that the legacy effect of statin during radiotherapy does not lower the subsequent risk of TIA and ischemic stroke in patient with HNC, which is contradictory to the report by Addison et al [ 1 ] Our study population, which comprised mostly of Asians, was different from that of Addison’s, and the different ethnic background may contribute to divergent statin resistance. Moreover, nasopharyngeal carcinoma consisted of a significant proportion of HNC in Taiwan [ 2 ].…”
contrasting
confidence: 99%
“…We read with great interest the study entitled “Incidental statin use and the risk of stroke or transient ischemic attack after radiotherapy for head and neck cancer” by Addison et al [ 1 ] The study, which included 1,011 head and neck cancer (HNC) patients with 288 (28%) on statins, found that statin was protective against the development of transient ischemic attack (TIA) and ischemic stroke after radiotherapy during a median followup of 3.4 years.…”
mentioning
confidence: 99%
“…13 The role of anticoagulation is uncertain and treatment strategies for CSMs (medical management and carotid intervention for atherosclerotic stroke and oral anticoagulants for cardioembolism) would be beneficial. 13,52 Routine vascular and electro-/echo-cardiographic studies are needed to rule out CSMs in patients with cancer and stroke.…”
Section: Exclusion Of Csmsmentioning
confidence: 99%
“…The adjusted HRs of CAS progression and IS were 0.62 (95% CI = 0.22-1.72; p = 0.36) and 0.26 (95% CI = 0.03-2.50; p = 0.24), respectively, in the HT patients without thyroxine supplement. Radiationinduced atherosclerosis could not be circumvented by atorvastatin [39] Statins were associated with a reduction in the combination of stroke and TIA (HR = 0.4; 95% CI = 0.2-0.8; p = 0.01) [41] Statins were associated with a signi cant reduction of 32% in stroke outcome alone (HR = 0.68, 95% CI = 0.48-0.98, p = 0.04) [44] Antiplatelet Anti-in ammatory and antithrombotic [38] Radiationinduced atherosclerosis could not be circumvented by aspirin and clopidogrel [38,39] No signi cant difference in the risk of IS or TIA between patients on continuous oral antithrombotic agents and nonusers (adjusted HR = 0.81; 95% CI = 0.20-3.31, p = 0.77) [42] Thyroxine May attenuate brosis response [31] NA No signi cant difference in stroke risk among patients with euthyroid or hypothyroidism using or not using thyroxine supplement (p = 0.31; our study)…”
Section: Resultsmentioning
confidence: 99%
“…In patients with severe CAS, carotid artery stenting seems to be bene cial for stroke prevention [36,37]. However, in the early post-RT vasculopathy phase, few interventions had been proved effective in curbing or slowing down disease progression [38][39][40][41][42]. In ammation, brosis, and endothelial proliferation play crucial roles in post-RT vasculopathy [12].…”
Section: Discussionmentioning
confidence: 99%